Agricultural Insurance in Latin America : Developing the Market - World Bank (World Bank, 2012)
The study focuses on how agricultural insurance can complement and enhance agricultural risk management in Latin America and Caribbean (LAC). The overall objective of this study is to provide the key elements for a strategy to increase the penetration of agricultural insurance in the region. The study is organized into five chapters, including this introduction. Chapter two provides an overview of the agricultural sector in LAC, including a description of the main farming systems and an assessment of the main perils affecting production. Chapter three describes the current provision of agricultural insurance, describing the evolution of agricultural insurance, providing the current market figures, assessing the availability of agricultural insurance products, describing government support to agricultural insurance, and estimating the current levels of penetration. Chapter four focuses on the challenges in attempting to increase coverage and penetration. It assesses the current gaps in the provision of agricultural insurance, identifies opportunities for further development, and recommends some future actions that can be taken. Finally, chapter five presents the conclusions of the study.